Spontaneous Coronary Dissection Review: A Complex Picture - Mario Bollati; Vincenzo Ercolano; Pietro Mazzarotto (Reviews in Cardiovascular Medicine)
Spontaneous coronary artery dissection (SCAD) represents a quite rare event but with potentially serious prognostic implications. Meanwhile, SCAD typically presents as an acute coronary syndrome (ACS). Despite the majority of SCAD presentation being characterized by typical ACS signs and symptoms, young age at presentation with an atypical atherosclerotic risk factor profile is responsible for late medical contact and misdiagnosis. The diagnostic algorithm is similar to that for ACS. Low-risk factors prevalence and young age would push toward non-invasive imaging (such as coronary computed tomography (CT)); instead, the gold standard diagnostic exam for SCAD is an invasive coronary angiography (ICA) due to its increased sensitivity and disease characterization. Moreover, intravascular imaging (IVI) improves ICA diagnostic performance, confirming the diagnosis and clarifying the disease mechanism. A SCAD–ICA classification recognizes four angiographic appearances according to lesion extension and features (radiolucent lumen, long and diffuse narrowing, focal stenosis, and vessel occlusion). Concerning its management, the preferred approach is conservative due to the high rates of spontaneous healing in the first months and the low rate of revascularization success (high complexity percutaneous coronary intervention (PCI) with dissection/hematoma extension risk). Revascularization is recommended in the presence of high-risk features (such as left main or multivessel involvement, hemodynamic instability, recurrent chest pain, or ST elevation). The first choice is PCI; coronary artery bypass graft (CABG) is considered only if PCI is not feasible or too hazardous according to the operators’ and centers’ experience. Medical therapy includes beta blockers in cases of ventricular dysfunction; however, no clear data are available about antiplatelet treatment because of the supposed risk of intramural hematoma enlargement. Furthermore, screening for extracardiac arthropathies or connective tissue diseases is recommended due to the hypothesized association with SCAD. Eventually, SCAD follow-up is important, considering the risk of SCAD recurrence. Considering the young age of patients with SCAD, subsequent care is essential (including psychological support, also for relatives) with the aim of safe and complete reintegration into a non-limited everyday life.